Teachers’ Self-Efficacy Based on Symptoms of Attention Deficit Hyperactivity Disorder in Primary School Pupils - Nataša Vlah; Tena Velki; Emina Kovačić (Center for Educational Policy Studies Journal)
Both the quality and quantity of teachers’ experiences of self-competence in dealing with pupils with symptoms of Attention Deficit Hyperactivity Disorder have been the subject of a great deal of research. The permanent monitoring of the levels at which teachers accomplish such competencies, which have a positive effect on the improvement of teaching, is one of the tasks of educational science. The present paper determines how teachers self-assess their efficacy in teaching pupils with behavioural difficulties based on the pupils’ symptoms of attention disorder and hyperactivity. Primary school teachers from 12 counties of the Republic of Croatia participated in the research. The teachers provided data for a total of 1,383 pupils in whom they subjectively detected behavioural difficulties. The research reveals that the characteristics of the pupil best predict the teacher’s self-efficacy. More time spent in the classroom with the teacher, better academic achievement, and a lower school grade indicate higher self-efficacy in teachers.